2007
DOI: 10.1038/sj.ijo.0803694
|View full text |Cite
|
Sign up to set email alerts
|

Plasma obestatin levels are lower in obese and post-gastrectomy subjects, but do not change in response to a meal

Abstract: Objective: To investigate a potential role for obestatin in humans by examining response to a fixed energy meal. Context: A new anorectic peptide hormone, obestatin has recently been isolated from rat stomach. The significance of this peptide in humans is unknown. Study design: Case-control study. Setting: Hospital-based study. Patients: Nine healthy controls, nine morbidly obese subjects and eight post-gastrectomy subjects. Intervention: Subjects attended after an overnight fast and were given a fixed energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 24 publications
7
51
0
2
Order By: Relevance
“…The plasma des-acyl ghrelin concentration significantly decreased after a meal, while the plasma obestatin concentration did not change. Human plasma obestatin concentration did not change even after intake of a 1550 kcal meal (Huda et al 2008). Thus, obestatin secretion does not appear to be influenced by dietary nutrients.…”
Section: Discussionmentioning
confidence: 76%
“…The plasma des-acyl ghrelin concentration significantly decreased after a meal, while the plasma obestatin concentration did not change. Human plasma obestatin concentration did not change even after intake of a 1550 kcal meal (Huda et al 2008). Thus, obestatin secretion does not appear to be influenced by dietary nutrients.…”
Section: Discussionmentioning
confidence: 76%
“…High levels of GPR39 mRNA were found abundantly in the amygdala, the hippocampus, and the auditory cortex but not in the hypothalamus Jackson et al, 2006). Plasma obestatin levels were lower in obese subjects and those who had undergone gastrectomy (Huda et al, 2008). However, recent studies indicate that obestatin is not the endogenous cognate ligand for GPR39 (Lauwers et al, 2006;Holst et al, 2007;Chartrel et al, 2007), whereas a more recent study demonstrated that obestatin was a metabolic hormone capable of binding to GPR39 and, in turn, of regulating the diverse biological functions of gastrointestinal and adipose tissues (Zhang et al, 2008a).…”
Section: Normal Physiology Of Obestatin and Regulation Of Its Expmentioning
confidence: 87%
“…However, recent studies indicate that obestatin is not the endogenous cognate ligand for GPR39 (Lauwers et al, 2006;Holst et al, 2007;Chartrel et al, 2007), whereas a more recent study demonstrated that obestatin was a metabolic hormone capable of binding to GPR39 and, in turn, of regulating the diverse biological functions of gastrointestinal and adipose tissues (Zhang et al, 2008a). The plasma obestatin concentration did not change after a 450-kcal (Mondal et al, 2008) or even a 1550-kcal (Huda et al, 2008) meal in humans, identifying that obestatin secretion is not influenced by dietary nutrients. The effects of obestatin on food intake 438 remain controversial .…”
Section: Normal Physiology Of Obestatin and Regulation Of Its Expmentioning
confidence: 93%
“…As a result, the effects of obestatin on food intake may be secondary to an action of the peptide to inhibit water drinking, a phenomenon known as dehydration anorexic effect [67]. Obestatin levels do not vary with a fixed energy meal, but are lower in obese subjects supporting a possible role for obestatin in long-term body weight regulation [115]. The effects of ghrelin, des-acyl ghrelin and obestatin in metabolism regulation are summarized in Table 1.…”
Section: Role Of Ghrelin and Obestatin In Me-tabolism And Appetite Rementioning
confidence: 99%